2020
DOI: 10.1021/acs.biochem.0c00341
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatics Plays a Crucial Role in HIV-1 Protease Substrate Binding, Drugs Fail to Take Advantage

Abstract: HIV-1 protease (HIVPR) is an important drug target for combating AIDS. This enzyme is an aspartyl protease that is functionally active in its dimeric form. Nuclear magnetic resonance reports have convincingly shown that a pseudosymmetry exists at the HIVPR active site, where only one of the two aspartates remains protonated over the pH range of 2.5–7.0. To date, all HIVPR-targeted drug design strategies focused on maximizing the size–shape complementarity and van der Waals interactions of the small molecule dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…12 It was also been shown that efficient drugs binding to HIV require specific electrostatic features. 13 Moreover, pH is well known to trigger several key biological events for viruses. For instance, a drop in pH is often used to allow the host penetration.…”
Section: Introductionmentioning
confidence: 99%
“…12 It was also been shown that efficient drugs binding to HIV require specific electrostatic features. 13 Moreover, pH is well known to trigger several key biological events for viruses. For instance, a drop in pH is often used to allow the host penetration.…”
Section: Introductionmentioning
confidence: 99%
“…Each monomer is made up of 99 amino acids and the active site located at the dimer interface is constituted by two catalytic aspartate residues, one from each monomer. [2][3][4] Currently, there are ten FDA approved drugs that act against HIVPR and all these drugs bind to the dimeric form of the enzyme. These drugs compete with the substrates for the binding to the active site of HIVPR dimer.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic interaction energies are usually the largest components of the interaction energy, followed by energies of exchange-repulsion, induction, and dispersion. Even if electrostatic interactions are not always the strongest one, due to being long-range and often directional, they make a dominant contribution to the relative orientation of the enzyme and substrate and therefore to molecular recognition and substrate specificity [30][31][32][33][34]. Electrostatic energies have also been shown to be a more reliable indicator of relative biding strength than more accurate total energies when dealing with questionable geometries [35].…”
Section: Introductionmentioning
confidence: 99%